2019
DOI: 10.1016/j.jhepr.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

HBeAg seroconversion is associated with a more effective PD-L1 blockade during chronic hepatitis B infection

Abstract: Background & Aims: Current therapies for chronic hepatitis B virus (HBV) infection control viral replication but do not eliminate the risk of progression to hepatocellular carcinoma. HBV-specific CD8 T cells are necessary for viral control, but they are rare and exhausted during chronic infection. Preclinical studies have shown that blockade of the PD-1:PD-L1 axis can restore HBV-specific T cell functionality. The aim of this study was to analyze how the clinical and treatment status of patients impacts the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Conversely, in a preclinical study of woodchucks, αPD-L1 monotherapy showed no efficacy; however, αPD-L1 plus ETV treatment reduced WHV DNA and WHsAg levels compared to ETV treatment alone, while both therapies were tolerable [ 139 ]. A recent study has shown that the inhibitory PD-1/PD-L1 axis is upregulated during CHB infection but not restored after successful antiretroviral therapy using NAs (undetectable viremia) [ 140 ]. In HBeAg-patients, treatment with monoclonal anti-PD-L1 antibodies (MEDI2790) increased HBV-specific T cell responses [ 140 ], while a phase Ib study found that the PD-1 inhibitor nivolumab (single dose, 0.1 or 0.3 mg/kg) was safe and well-tolerated with or without a therapeutic vaccine (GS-4774) [ 84 ] and decreased HBsAg titers by 0.5 log at 24 week, achieving sustained HBsAg loss and seroconversion in one patient [ 84 ].…”
Section: Adaptive Immune Response Modulationmentioning
confidence: 99%
“…Conversely, in a preclinical study of woodchucks, αPD-L1 monotherapy showed no efficacy; however, αPD-L1 plus ETV treatment reduced WHV DNA and WHsAg levels compared to ETV treatment alone, while both therapies were tolerable [ 139 ]. A recent study has shown that the inhibitory PD-1/PD-L1 axis is upregulated during CHB infection but not restored after successful antiretroviral therapy using NAs (undetectable viremia) [ 140 ]. In HBeAg-patients, treatment with monoclonal anti-PD-L1 antibodies (MEDI2790) increased HBV-specific T cell responses [ 140 ], while a phase Ib study found that the PD-1 inhibitor nivolumab (single dose, 0.1 or 0.3 mg/kg) was safe and well-tolerated with or without a therapeutic vaccine (GS-4774) [ 84 ] and decreased HBsAg titers by 0.5 log at 24 week, achieving sustained HBsAg loss and seroconversion in one patient [ 84 ].…”
Section: Adaptive Immune Response Modulationmentioning
confidence: 99%
“…This effect was linked to intermediate T cell differentiation [50]. The effect of PD-1 blockade on HBV-specific CD8+ T cells from blood and liver of chronically infected patients could in some cases be boosted by the addition of CD137L [51,52] and was shown to be more efficient in HBeAg+ patients [53]. But not only CD8+ T cells are affected by checkpoint inhibitors.…”
Section: Induction Of the Adaptive Immune Systemmentioning
confidence: 99%
“… 19 , 29 , 30 , 31 Although TLR7 agonists would not directly lower HBsAg, it has been suggested that TLR7 agonists could be used effectively in combination with direct‐acting antivirals or drugs that have complementary immunomodulatory activity. 19 , 32 , 33 , 34 This concept remains to be determined in the phase II setting and clinical trials are currently ongoing in patients with CHB to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Promising antiviral activity has been observed with TLR7 agonists in preclinical models of HBV, 18,27,28 but significant HBsAg decline has yet to be demonstrated with TLR7 agonists administered alone or in combination with NUCs in the clinical CHB setting 19,29–31 . Although TLR7 agonists would not directly lower HBsAg, it has been suggested that TLR7 agonists could be used effectively in combination with direct‐acting antivirals or drugs that have complementary immunomodulatory activity 19,32–34 . This concept remains to be determined in the phase II setting and clinical trials are currently ongoing in patients with CHB to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%